The Beauty of a Local Brand that Becomes Queen in Its Own Country: A Brandmorphosis Analysis of Wardah - Retno Wulandari; Asep Rahmat Ghofur; Walid Adriansyah (Graduate School of Communication Universitas Bakrie, 2022)
Along with the development of the times, cosmetics have become a necessity that is no longer trivial. It is not surprising that many cosmetic products have emerged on the market. With so many competitors, cosmetic companies must develop branding strategies to build brand trust and create sustainable businesses. One of the cosmetic brands that has long been involved in the national cosmetics world and has become a market leader in Indonesia is Wardah. This article discusses how brandmorphosis or a description of the journey, evaluation, and metamorphosis of the development of the Wardah as a local brand to become a cosmetic market leader in Indonesia. The method used in this study is Brandmorphosis Analysis with a qualitative approach and data sourced from a collection of journal articles, books, and news. The results obtained by Wardah have successfully undergone a business transformation, including re-branding, adding products, changing marketing strategies, and expanding into the digital market. In addition, Wardah has also succeeded in maintaining consumer trust with a commitment to the halal concept, a significant factor in the Indonesian market due to the large Muslim population, and good product quality